Informal environmental learning: the sustaining nature of daily child/water/dirt relations. Issue 9 (2nd October 2020) - Crinall, Sarah; Somerville, Margaret
Abstract: This post-inquiry paper looks to the intimate matter of young children and their worlds outside of school. With new materialism, water and art as philosophical muse, a new kind of 'sustaining nature' for environmental education emerges, problematizing 'sustainability' as an aim. We gathered and exchanged short videos and field notes (iPhone artifacts) during morning and afternoon walks with young children in our everyday lives. In a playful moment, these are engaged with in relation to theoretical material on 'art and sensation' from philosophers, Deleuze (2003 ), Grosz (2008 ) and ontologies of water that do post-qualitative research playfully (Crinall 2017 ; Somerville 2017 ). We mutually emerge with relational pedagogies, conjuring the grace and gift of daily life with the matter of clay, dirt, deadbird, water, and home into an environmental learning that attunes bodies/minds to the significance, grace and gift of sustaining, artful everyday life.